ANALISIS HARGA SAHAM, VOLUME PERDAGANGAN SAHAM DAN VARIAN RETURN SAHAM TERHADAP BID ASK SPREAD PADA MASA SEBELUM DAN SESUDAH STOCK SPLIT PADA PERUSAHAAN YANG TERDAFTAR DI BEI TAHUN 2011 – 2015 - Kevin Immanuel; Oktafalia Marisa Muzamil (Jurnal Akuntansi Bisnis, 2018)
The stock split policy is taken by the company to keep stock prices not too high so that its stock can reach many investors and increase stock liquidity. This study also aims to measure whether there is a difference before and after the company does a stock split through bid ask spread.This research method uses event study about market reaction to information from stock split announcement.This type of research includes descriptive research using quantitative data, while data collection techniques consist of library techniques and documentation techniques. The results showed that the test for normality only trading volume activity (TVA) that qualify and can do paired samples t-test, while the stock price, the variant return and bid ask spread is done by using Wilcoxon test because it does not pass the test of normality. In the paired sample t-test, the results show that there is significant trading activity volume difference before and after stock split. In the Wilcoxon test, the results show that there is no significant price difference before and after stock split, there is no significant difference of return variance before and after stock split, and there is no significant bid ask spread before And after stock splits.The conclusions can be drawn based on the results of the study that the market conditions are in the bearish market and investors do not provide a quick feedback to the stock split. However, stock splits have increased liquidity from firms due to stock splits to n per sheets and reduced asymmetry costs to be borne by investors. Suggestions from researchers to investors are investors can take advantage of stock split events and must be observant in seeing the stock of a particular company that has prospects, good performance and good reputation in the community. For the company, the company should be wise in determining the ratio for stock prices to be optimal and consider whether the stock market is bearish / bullish market when doing stock split policy.Keywords: stock prices, return, trading volume activity, bid ask spread, and stock split